2022
DOI: 10.1038/s41598-022-06304-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and optimization studies of polypropylene hybrid biocomposites

Abstract: Towards developing a polymeric matrix characterized by high strength to cost ratio, polypropylene (PP) was hybridized with low-cost particulate snail shell (PSS) and kenaf fiber (KF) via compression moulding at 180 °C and 0.2 MPa. The developed composites were grouped into three and labeled as mix 2, 4, and 10. Each group entailed the blend of 5, 10, 20, and 30 wt% KF with 2, 4, 10 wt% PSS respectively. From the results, it is observed that the hardness value was enhanced by the blend of 5 to 30 wt% KF and 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…PP is influenced by thermo-oxidative and UV light-initiated degradation in warm and bright environments leading to chain scission and thus to molar mass reduction and MFR increase [16]. This effect in combination with the influence of material changes on thermal and mechanical properties is already discussed in the literature by parametrization of different formulations [17][18][19][20][21][22][23]. Nevertheless, this paper discusses MFR value changes as they are of most importance for machine operators.…”
Section: Introductionmentioning
confidence: 99%
“…PP is influenced by thermo-oxidative and UV light-initiated degradation in warm and bright environments leading to chain scission and thus to molar mass reduction and MFR increase [16]. This effect in combination with the influence of material changes on thermal and mechanical properties is already discussed in the literature by parametrization of different formulations [17][18][19][20][21][22][23]. Nevertheless, this paper discusses MFR value changes as they are of most importance for machine operators.…”
Section: Introductionmentioning
confidence: 99%
“…The work established that optimum parameters were content of TiO 2 at 5%, barrel temperature of 225 0 C, residence time of 30 minutes and holding time of 20 s. Adediran et al optimized mechanical properties of hybrid propylene reinforced bio composites using Taguchi model. It was found that collage of 4% PSS and 1o% kenaf fibre produced the optimum combination for hybrid bio composites 22 . Besides this, Taguchi method hybridized with grey relational grade has as well been employed for multi-response optimization of wire discharge electrical discharge machining 23 , turning process 24 and milling parameter 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The work established that optimum parameters were content of TiO 2 at 5%, barrel temperature of 225 °C, residence time of 30 min and holding time of 20 s. Adediran et al optimized mechanical properties of hybrid propylene reinforced bio composites using Taguchi model. It was found that collage of 4% PSS and 10% kenaf fibre produced the optimum combination for hybrid bio composites 22 . Besides this, Taguchi method hybridized with grey relational grade has as well been employed for multi-response optimization of wire discharge electrical discharge machining 23 , turning process 24 and milling parameter 25 .…”
Section: Introductionmentioning
confidence: 99%